SAT0301 Serum autoantibody profiling of primary sjÖgren's syndrome patients reveals novel biomarkers associated with the disease, disease activity, and clinical response to vay736. (15th June 2017) - Budde, P; Doucet, J; Zucht, H-D; Kazma, R; Maguire, P; Avrameas, A; Valentin, M-A; Oliver, S; Schulz-Knappe, P; Vitaliti, A
Abstract : Background: Overexpression of B cell activating factor (BAFF) in salivary glands contributes to the pathogenesis of primary Sjögren's syndrome (pSS) by promoting autoantibody (AAB) production. Treatment of pSS patients with VAY736, an anti-BAFF receptor mAb, appears promising and was associated with a depletion of circulating B cells and a positive therapeutic effect [1]. In addition to the classical anti-SS-A/Ro and anti-SS-B/La, a broader set of AABs may reflect B cell disturbances in pSS and could serve as markers during clinical development of novel pSS therapeutics. Objectives: In this study, we explored novel AABs in pSS patients and healthy controls (HCs) and we tested their associations with the disease, disease activity, and clinical response to VAY736. Methods: Reactivity of AABs to 1, 596 antigens was measured in serum samples from 27 pSS patients from a placebo-controlled trial at baseline and post-treatment week 12 and from 50 age and gender-matched HCs. Patients were treated at baseline with a single dose of VAY736 at 10 mg/kg (n=12), 3 mg/kg (n=6), or placebo (n=9). First, to identify AABs associated with pSS, 3 different methods compared AAB levels at baseline between pSS patients and HCs: Wilcoxon rank sum test, significance analysis of microarrays, and comparison of the 90th quantiles between groups. Second, to identify AABs associated with pSS activity, Pearson correlation of AABs with EULAR Sjögren's Syndrome Disease Activity Index, secondary outcomes, and salivary and serum BAFF were tested, using baseline and week 12 levels as well as relative changes. Third, VAY736 treatment-specific changes in AAB levels were investigated using linear mixed-effects models adjusting for dosage, age, and gender effects. Results: Of 1, 596 antigens, 36 were statistically different between pSS patients and HCs for at least one of the 3 tests, including the known SS-A/Ro and SS-B/La (significant for all 3 tests) as well as novel antigens. SS-A/Ro and SS-B/La AABs were not associated with disease activity or response to treatment. However, 48 AABs were significantly correlated with pSS activity combining all treatment arms, and 12 AABs had baseline values that correlated with change in pSS activity upon VAY736 treatment (unadjusted p<0.05). Interestingly, 51 serum AABs correlated with BAFF saliva levels (|r|>0.55), but not with BAFF serum levels. The genes encoding novel antigens are involved in apoptotic, anti-viral, metabolic, inflammatory, blood coagulation and B-cell processes, suggesting a possible link to the disease pathology. Finally, there was no reduction in AABs levels in response to VAY736, possibly because the 12 weeks post-treatment analysis was too short to identify large effects. Conclusions: In conclusion, we identified new AABs in pSS patients that have the potential to serve as markers of diagnosis, pSS activity, or as predictors of clinical outcome measures. Further large-scale studies are needed to confirm the value of these markers. References: Dörner T et al. Arthritis Rheum 2016; 68(suppl S10):4051. Disclosure of Interest: P. Budde Employee of: Protagen AG, J. Doucet Employee of: Novartis AG, H.-D. Zucht Employee of: Protagen AG, R. Kazma Employee of: Novartis AG, P. Maguire Employee of: Novartis AG, A. Avrameas Employee of: Novartis AG, M.-A. Valentin Employee of: Novartis AG, S. Oliver Employee of: Novartis AG, P. Schulz-Knappe Employee of: Protagen AG, A. Vitaliti Employee of: Novartis AG